COMPARISON OF URINE WITH PLASMA NEUTROPHIL GELATINASE– ASSOCIATED LIPOCALIN IN DETECTING ACUTE KIDNEY INJURY AFTER CARDIOPULMONARY BYPASS SURGERY: Plasma Neutrophil Gelatinase - Khan, Brig Dilshad Ahmed; Munir, Muhammad Usman; Khan, Farooq Ahmad; Naqvi, Syed Muhammad Shahab (Pakistan Armed Forces Medical Journal, 2013)
Objective: To compare the accuracy of urine with plasma neutrophil gelatinase-associated lipocalin (NGAL) in early detection of acute kidney injury (AKI) following cardiopulmonary bypass (CPB) surgery.Study Design: A prospective cohort study.Place and duration of study: Department of Chemical Pathology and Endocrinology, AFIP from December 2011 to July 2012.Patients and Methods: Ninety three adult patients planned for CPB surgery in AFIC/NIHD were consecutively included. Blood for serum creatinine were collected preoperatively, 4, 24 & 48 hours (h) after CPB surgery. Blood and urine samples for NGAL analysis were collected only at 4 h. Serum creatinine, plasma and urine NGAL samples were analyzed on UniCel® DxC 600 (Beckman), TRIAGE meter pro (Biosite) and ARCHITECT i2000SR analyzer (Abbott) respectively.Results: Out of 93 patients undergoing CPB surgery, 12 (13%) developed AKI. AKI patients had significantly higher median interquartile range (IQR) urine NGAL of 180 ng/ml (105-277 ng/ml) as compared to control of 6 ng/ml (2-15 ng/ml) and median plasma NGAL of 170 ng/ml (126-274 ng/ml) as compared to control of 75 ng/ml (61-131 ng/ml). The patients had increased urine vs plasma NGAL area under curve (AUC) [ 0.91 vs 0.70 (p =